PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL KIREI BANTAENG - Sudirman Sudirman; A. Baddrusaman (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the effect of service quality on customer satisfaction at the Kirei Bantaeng Hotel. This type of research used in this study is a quantitative method with a sample size of 100 respondents. Data obtained from the results of questionnaires distributed to customers of Hotel Kirei Bantaeng. The data analysis technique uses validity test, reliability test, simple linear regression test, partial test and determination coefficient test. The value of the coefficient of determination (R^2) is 0.136, so it can be seen that the effect of Service Quality on Customer Satisfaction is 13.6%. In the t test results, the coefficient value of the service quality variable is 0.287 with a significant value of 0.000 (0.000 <0.05), and the t value is greater than the t table (3.925> 1.98). The results showed that the hypothesis can be accepted because service quality has a positive and significant effect on customer satisfaction.